Flexible and transparent polymer/cellulose nanocrystal nanocomposites with high thermal conductivity for thermal management application. Issue 28 (27th December 2019) - Wu, Xinfeng; Gao, Yuan; Yao, Hang; Sun, Kai; Fan, Runhua; Li, Xiaofeng; An, Yan; Lei, Yanhua; Zhang, Yuliang
ABSTRACT: Polymeric materials play important roles in semiconductor technology and modern electronic devices. However, the weak thermal management capability of polymer seriously restricts the service life, reliability, and efficiency of devices. Consequently, inorganic or metallic thermally conductive fillers are added into polymers to make up the low thermal conductivity, but the optical transparency and flexibility always decrease or even disappear. Herein, we report transparent polymer nanocomposites comprising poly(vinyl alcohol) (PVA) and cellulose nanocrystal (CNC) with highly lateral thermal conductivity [about 5.7 W/(m·K)]. Such a high thermal conductivity is attributed to the aligned structure of CNC in PVA matrix and hydrogen‐bond interaction between CNC and PVA. All the organic nanocomposites also present excellent electrical insulating performance and tensile properties. The transparent and flexible nanocomposites are promising in the thermal management applications of displays, next‐generation wearable devices, sensors, and LEDs. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48864. Abstract :